2011
DOI: 10.1371/journal.pone.0018064
|View full text |Cite
|
Sign up to set email alerts
|

Deregulation of MYCN, LIN28B and LET7 in a Molecular Subtype of Aggressive High-Grade Serous Ovarian Cancers

Abstract: Molecular subtypes of serous ovarian cancer have been recently described. Using data from independent datasets including over 900 primary tumour samples, we show that deregulation of the Let-7 pathway is specifically associated with the C5 molecular subtype of serous ovarian cancer. DNA copy number and gene expression of HMGA2, alleles of Let-7, LIN28, LIN28B, MYC, MYCN, DICER1, and RNASEN were measured using microarray and quantitative reverse transcriptase PCR. Immunohistochemistry was performed on 127 sampl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

17
178
0
6

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 190 publications
(201 citation statements)
references
References 43 publications
17
178
0
6
Order By: Relevance
“…In fact, we have previously identified four LIN28A regulatory miRNAs that were globally down-regulated in human tumors (67). In addition, overexpression of LIN28 activators, such as the Myc oncogene (47,54,68), may serve as another mechanism to deregulate LIN28A expression in epithelial tumors.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In fact, we have previously identified four LIN28A regulatory miRNAs that were globally down-regulated in human tumors (67). In addition, overexpression of LIN28 activators, such as the Myc oncogene (47,54,68), may serve as another mechanism to deregulate LIN28A expression in epithelial tumors.…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that both expression of LIN28A and LIN28B are reac- (4,(42)(43)(44)(45)(46)(47). However, the expression and distribution of LIN28A in different types of epithelial tumors is still unknown.…”
Section: Reactivation Of Strong Lin28a Expression In 10% Of Humanmentioning
confidence: 99%
See 1 more Smart Citation
“…Expression profiling of large cohorts of HGSOC tumors have pointed to the existence of four distinct molecular subtypes (3,31), which collectively exhibit diverse pathological and clinical features (3,31,32). Notably, a molecular HGSOC subset, i.e., C5, has been defined by high level MYCN expression, which correlates with poor prognosis (32).…”
Section: Discussionmentioning
confidence: 99%
“…The involvement of the LIN-28B/let-7 axis in cancer has also been studied in vivo neuroblastoma animal model; LIN-28B overexpression-induced neuroblastma had markedly low levels of let-7 miRNA and high levels of MYC protein [13]. Frequent dysregulation of LIN-28B in human cancers including liver, breast, and ovary suggests that LIN-28B functions as an oncogene [2,6,11,14,15], influencing disease prognosis and patient response to treatment [5].…”
Section: Introductionmentioning
confidence: 99%